Determining the tourist attractive regions by GIS analysis using heatmaps - Kulyk, Viktoriya; Sossa, Rostyslav (Geodesy and Cartography, 2018)
In this article, we explore heatmaps as a method of applying GIS-technologies to study the distribution of tourist and recreational objects. We analyze the foundations of heatmaps, their features and advantages among the cartographic methods of research, and examples of their application in the tourism industry. Using a database in QGIS, we create heatmaps of tourist objects in Ukraine that help to determine and visualize the tourist attractive regions of the country.